ENHANCING ESL SPEAKING SKILLS THROUGH ROLE-PLAYING: INSIGHTS FROM EXISTING RESEARCH - Jenny Helvira; Enmia Munte; Honey Marbun; Gracya Sibarani; Meisuri Meisuri (Adisam Publisher, 2025)
Speaking proficiency is a critical component of English as a Second Language (ESL) learning, yet many students struggle with confidence and fluency due to limited speaking practice, fear of mistakes, and lack of real-life conversational exposure. Traditional teaching methods often emphasize grammar, reading, and writing over spoken communication, further hindering students’ ability to engage in spontaneous conversations. Role-playing has emerged as an effective communicative strategy that provides structured yet dynamic opportunities for students to develop their speaking skills in realistic contexts. This study reviews existing literature to examine the impact of role-playing on ESL learners' confidence, fluency, vocabulary retention, and engagement. The findings indicate that role-playing fosters a supportive learning environment, reduces speaking anxiety, enhances spontaneous speech, and improves vocabulary acquisition through contextual application. However, challenges such as classroom management and varying proficiency levels require structured guidance from teachers. This study highlights the pedagogical benefits of integrating role-playing into ESL instruction and calls for further research on its long-term effects in diverse learning contexts.